Human Islet Amyloid Polypeptide Fibril Binding to Catalase: A Transmission Electron Microscopy and Microplate Study - Nathaniel G. N. Milton; J. Robin Harris (The Scientific World Journal)
The diabetes-associated human islet amyloid polypeptide (IAPP) is a 37-amino-acid peptide that forms fibrils in vitro and in vivo. Human IAPP fibrils are toxic in a similar manner to Alzheimer's amyloid-β (Aβ) and prion protein (PrP) fibrils. Previous studies have shown that catalase binds to Aβ fibrils and appears to recognize a region containing the Gly-Ala-Ile-Ile sequence that is similar to the Gly-Ala-Ile-Leu sequence found in human IAPP residues 24-27. This study presents a transmission electron microscopy (TEM)—based analysis of fibril formation and the binding of human erythrocyte catalase to IAPP fibrils. The results show that human IAPP 1-37, 8-37, and 20-29 peptides form fibrils with diverse and polymorphic structures. All three forms of IAPP bound catalase, and complexes of IAPP 1-37 or 8-37 with catalase were identified by immunoassay. The binding of biotinylated IAPP to catalase was high affinity with a KD of 0.77nM, and could be inhibited by either human or rat IAPP 1-37 and 8-37 forms. Fibrils formed by the PrP 118-135 peptide with a Gly-Ala-Val-Val sequence also bound catalase. These results suggest that catalase recognizes a Gly-Ala-Ile-Leu—like sequence in amyloid fibril-forming peptides. For IAPP 1-37 and 8-37, the catalase binding was primarily directed towards fibrillar rather than ribbon-like structures, suggesting differences in the accessibility of the human IAPP 24-27 Gly-Ala-Ile-Leu region. This suggests that catalase may be able to discriminate between different structural forms of IAPP fibrils. The ability of catalase to bind IAPP, Aβ, and PrP fibrils demonstrates the presence of similar accessible structural motifs that may be targets for antiamyloid therapeutic development.